Simulated effects of releasing pen‐raised deer into the wild to alter population‐level antler size - Stephen Demarais; Bronson K. Strickland; Stephen L. Webb; Trent Smith; Chris Mcdonald (Wildlife Society Bulletin)
ABSTRACT The ability to develop large antlers in penned deer (Odocoileus sp.) has increased interest in releasing pen‐raised deer to increase antler size of wild populations. We used a model based on population genetic theory with random removal as the form of population control and either 10% emigration and 10% immigration to represent a free‐ranging population (Free Range) or with no egress or ingress to represent a fenced property (Fenced). We compared results with a livestock model with no egress or ingress and selective removal of smaller antlered males as the form of population control (Best Case). We modeled release of fawns with an antler distribution averaging 200 gross Boone and Crockett (B&C) score at 5 rates (1%, 5%, 10%, 25%, and 50% replacement of existing population of 2,000) and report the change from a population average of 127.5. The impact of releasing pen‐raised deer into native populations was minimal below 25% replacement rate. Replacing 5% of a free‐ranging population with 100 pen‐raised deer increased B&C score by 0.8, whereas replacing 25% with 500 pen‐raised deer increased score by 12. Releasing pen‐raised deer into a fenced property was 50% more effective; a 25% replacement increased score by 18. The Best Case Model increased score by 33 at 25% replacement. The cost for each unit increase in score was US$115,000 in a free‐ranging population, US$75,000 in a fenced population, and US$33,000 in the best case. Our results suggest that altering genetic composition of white‐tailed deer populations is not feasible for free‐ranging populations and very costly within fenced populations. © 2016 The Authors. Wildlife Society Bulletin published by Wiley Periodicals, Inc. on behalf of The Wildlife Society.